Cost effectiveness of extended treatment with low molecular weight heparin (dalteparin) in unstable coronary artery disease: results from the FRISC II trial. Issue 3 (1st March 2003) - Janzon, M; Levin, L-Å; Swahn, E
Abstract : Background: In unstable coronary artery disease short term treatment with low molecular weight heparin in addition to aspirin has been shown to be effective. Objective: To assess the cost effectiveness of extended treatment with dalteparin in patients managed with a non-invasive treatment strategy. Design: Prospective, randomised, multicentre study. Setting: 58 centres in Sweden, Denmark, and Norway, of which 16 were interventional. Patients: After at least five days' treatment with open label dalteparin, 2267 patients were randomised to continue double blind treatment with either subcutaneous dalteparin twice daily or placebo for three months. The patients' use of health service resources was recorded prospectively. Main outcome measure: Death/myocardial infarction. Results: After one month into the double blind period there was a 47% relative reduction in death or myocardial infarction in the dalteparin group compared with the placebo group (p = 0.002). There was a non-significant mean cost difference, favouring the placebo group, of 849 Swedish crowns (SEK) per patient (equivalent to £58). The incremental cost effectiveness ratio for giving dalteparin treatment for one month was SEK 30 300 (range −78 000 to 139 000) (£2060, range −£5300 to £9400) per avoided death or myocardial infarct. At three months, the decrease in death or myocardial infarction was not significant, precluding cost effectiveness analyses. Conclusions: There is a marginal and non-significant increase in costs for one month of extended dalteparin treatment compared with placebo. Extended dalteparin treatment lowers the risk of death or myocardial infarction in patients with unstable coronary artery disease. While in many countries the resources for early intervention are limited, extended dalteparin treatment up to one month is a cost effective bridge to invasive intervention.